A Dual Peptide Sustained-Release System Based on Nanohydroxyapatite/Polyamide 66 Scaffold for Synergistic-Enhancing Diabetic Rats’ Fracture Healing in Osteogenesis and Angiogenesis - Li, Jian; Wei, Jiaxing; Li, Ang; Liu, Hongyu; Sun, Jingxue; Qiao, Hong (Frontiers in Bioengineering and Biotechnology, 2021)
Diabetes mellitus impairs fracture healing and function of stem cells related to bone regeneration, thus effective bone tissue engineering therapies can intervene those dysfunctions. Nanohydroxyapatite/polyamide 66 (n-HA/PA66) scaffold has been used in fracture healing, whereas the low bioactivity limits its further application. Herein, we developed a novel bone morphogenetic protein-2- (BMP-2) and vascular endothelial growth factor- (VEGF) derived peptides-decorated n-HA/PA66 (BVHP66) scaffold for diabetic fracture. The n-HA/PA66 scaffold was functionalized by covalent grafting of BMP-2 and VEGF peptides to construct a dual peptide sustained-release system. The structural characteristics and peptide release profiles of BVHP66 scaffold were tested by scanning electronic microscopy, fourier transform infrared spectroscopy, and fluorescence microscope. Under high glucose condition, the effect of BVHP66 scaffold on rat bone marrow mesenchymal stem cells’ (rBMSCs) adherent, proliferative and differentiate capacities and human umbilical vein endothelial cells’ (HUVECs) proliferative and tube-formation capacities was assessed. Finally, the BVHP66 scaffold was applied to fracture of diabetic rats, and its effect on osteogenesis and angiogenesis was evaluated. In vitro, the peptide loaded on the BVHP66 scaffold was in a sustained-release mode of 14 days. The BVHP66 scaffold significantly promoted rBMSCs and HUVECs’ proliferation, and improved osteogenic differentiation of rBMSCs and tube-formation of HUVECs in high glucose environment. In vivo, the BVHP66 scaffold enhanced osteogenesis and angiogenesis, rescuing the poor fracture healing in diabetic rats. Comparing to single peptide modification, the dual peptide-modified scaffold had a synergetic effect on bone regeneration in vivo. Overall, this study reported a novel BVHP66 scaffold with excellent biocompatibility and bioactive property and its application in diabetic fracture.